2008
DOI: 10.1093/glycob/cwn127
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel gene encoding the trehalose phosphate synthase in the cotton bollworm, Helicoverpa armigera

Abstract: Trehalose and trehalose metabolism are crucial for insect development. We measured the content of polyhydric compounds in the hemolymph of diapause- and nondiapause-destined individuals of Helicoverpa armigera. We found that the trehalose content is much higher in diapause-destined individuals than that in nondiapause individuals. The activity of trehalose-6-phosphate synthase (TPS) during H. armigera larval-pupal development is significantly higher in diapause-type individuals and is closely correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 29 publications
4
61
2
Order By: Relevance
“…It is reported that SexTPS is specifically expressed in the fat body and ovaries in larval stages, which is consistent with the results of studies on H. armigera (Xu et al, 2009, Tang et al, 2010. In Locusta migratoria, TPS is expressed not only in the fat body, but also in gut, hemolymph, and leg muscle (Cui & Xia, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is reported that SexTPS is specifically expressed in the fat body and ovaries in larval stages, which is consistent with the results of studies on H. armigera (Xu et al, 2009, Tang et al, 2010. In Locusta migratoria, TPS is expressed not only in the fat body, but also in gut, hemolymph, and leg muscle (Cui & Xia, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…In non-diapausing and diapausing H. armigera, HarTPS mRNA expression was low and high, respectively (Xu et al, 2009). In addition, in S. exigua, semiquantitative RT-PCR results reveal that SexTPS mRNA is expressed in fat body at different levels from fifth instar larvae to pupae (Tang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalose is the major sugar in the blood for insect growth and development; it is also thought to be involved in response to environmental stresses, including heat, cold, desiccation, and oxidation (Elbein et al, 2003). The up-regulation of this transcript contributes to the increase of trehalose content, which is most likely a response to a temperature cue and acts as a cryotectant in some insect species, including onion maggot (Nomura and Ishikawa, 2001) and cotton bollworm (Xu et al, 2009). Based on this preliminary result, we thought trehalose-6-phosphate synthase, serving as cryotectant or energy and carbon reserve, would play am important role in wintering survival of onion maggot.…”
Section: Discussionmentioning
confidence: 99%
“…In metazoans, the tps gene has been found in several arthropods (Chen et al 2002;Chung 2008;Clark et al 2009;Xu et al 2009) and desiccation intolerant and tolerant nematodes (Pellerone et al 2003;Goyal et al 2005a). However, its presence in desiccation tolerant animals is not universal, as the tps gene was not found in anhydrobiotic bdelloid rotifers (Lapinski & Tunnacliffe 2003).…”
Section: Introductionmentioning
confidence: 99%